The less is more garden : big ideas for designing your small yard - Morrison, Susan, 1963- (Timber Press, 2018)
When it comes to gardens, bigger isn't always better. A smaller space requires fewer plants and less time to design, install, and maintain. The Less Is More Garden shows you how to take advantage of every square foot of space. Designer Susan Morrison offers savvy tips to match your landscape to your lifestyle, draws on years of experience to recommend smart plants with seasonal interest, and suggests hardscape materials to personalize your space. Inspiring photographs highlight a variety of inspiring small-space designs from around the country. With The Less Is More Garden, you'll see how limited space can mean unlimited opportunities for gorgeous garden design.